INNOVATIVE TEACHING TECHNOLOGIES IN THE DEVELOPMENT OF EDUCATIONAL ACTIVITIES OF STUDENTS OF TECHNICAL HIGHER EDUCATION INSTITUTIONS - Saparova Ayzada Alauatdin qizi (Modern American Journals, 2025)
The article examines the role and effectiveness of innovative teaching technologies in enhancing the educational activities of students in technical higher education institutions. As the demands of the 21st-century knowledge economy continue to evolve, engineering and technology students are expected not only to master theoretical knowledge but also to develop problem-solving skills, adaptability, and collaborative competencies. Innovative teaching methods—such as blended learning, project-based learning, flipped classrooms, virtual laboratories, and AI-driven educational platforms—offer transformative potential to make learning more interactive, personalized, and aligned with real-world challenges. The research aims to identify, analyze, and evaluate the impact of such pedagogical innovations on student engagement, academic performance, and the formation of professional competencies in technical fields. The findings will contribute to the optimization of teaching practices and curricular design in engineering education.
Keywords: innovative, teaching technologies, educational activities, students, technical, higher education, institutions, engineering education.